ASSESSING TECHNICAL TEACHERS’ PROFESSIONAL DEVELOPMENT IN INFORMATION AND COMMUNICATION TECHNOLOGY FOR TEACHING IN POLYTECHNICS IN THE NORTH EASTERN STATES OF NIGERIA - Tumba, Ishaya; Michika, Mohammed Usman (European Scientific Journal, ESJ, 2014)
This study was designed to assess the level of preparedness of technical teachers to use information and communication technology facilities for teaching in Polytechnics in the North Eastern States of Nigeria. The study adopted descriptive survey research design to collect opinions of technical teachers on their professional development in information and communication technology and their exposure to information and communication technology facilities used for teaching. A 5-point researcher made questionnaire was used for data collection. The instrument was validated by two experts in information and communication technology and it was also pilot tested on nine polytechnic teachers after which a reliability coefficient of 0.98 was estimated. Two research questions were raised and one hypothesis propounded. The study revealed that technical teachers teaching in polytechnics in the North Eastern States of Nigeria possess moderate professional development and exposure to information and communication technology facilities. This implies that the teachers need further training on information and communication technology facilities used in the classroom. It was then recommended that employers of the teachers should send them on in-service training in information and communication technology and to also put in place adequate information and communication technology facilities for instructional purpose. The study suggested further studies to investigate the teachers’ level of competency in using information and communication technology in the classroom.